Canberra's early years photographs from the Mildenhall Collection. ([Australia] : Australian Archives, 1997)
Shows a photograph of two girls wearing hats and standing in an arched window looking out. They appear to be standing on a table. Maroon border.
"7 May - 7 September 1997 Old Parliament House".
Catalogue record generated as part of a batch load.
Keywords: Australian Archives -- Posters; Canberra (A.C.T.) -- History -- Posters